Orbital Metastasis as Initial Clinical Presentation in a Patient of Hepatocellular Carcinoma – A Rare Case with Review of Literature - Rana, Sakshi; Khosla, Divya; Periasamy, Kannan; Kapoor, Rakesh; Bhardwaj, Sunny; Madan, Renu; Goyal, Shikha; Rajwanshi, Arvind (Indian Journal of Medical and Paediatric Oncology, 2021)
Orbital metastasis, as the initial clinical presentation in hepatocellular carcinoma (HCC), is a rare manifestation. A 66-year-old male patient presented with a history of protrusion of the eyeballs, double vision, and swelling over the left side of the head for 8 months. Magnetic resonance imaging of the brain with orbit revealed a heterogeneous lesion in the left frontal lobe causing its destruction with intraorbital and intracranial extension. Triphasic contrast-enhanced computed tomography was suggestive of multiple hypodense areas in both lobes of the liver. Tissue diagnosis from the liver was suggestive of HCC. A diagnosis of multifocal HCC with orbital metastasis was made. The patient was treated with palliative radiotherapy and sorafenib. Orbital metastasis in HCC is rare. Prognosis is somber in such cases. The treatment should focus on providing palliation from symptoms.
Keywords: hepatocellular carcinoma; metastasis; orbital; palliation; radiotherapy